Georadar investigations and geochemical analysis in contemporary archeological studies - ŁYSKOWSKI, Mikołaj; WARDAS-LASOŃ, Marta (Geology, Geophysics and Environment, 2012)
Archeological studies require a precise and interdisciplinary approach. Use of the noninvasive methods in urban area investigations is expected because they do not result in any changes in land architecture plans. Very good combination fulfilling such demands are geochemical analyses of: pH, Eh, conductivity and heavy metals concentrations in soils and the results of the ground penetrating radar method. These methods allow for a more precise selection of places of interest and can be also used for a more accurate calibration and better interpretation of subsequent results. Proposed methodology gives good final results thanks to complementarity of each method and can be used under variable conditions.